Development of Sociocultural-Based Reflective Picture Book Media to Improve Social Skills and Reading Interest - Hartati, Eti; Nasucha, Muntoha; Kusrina, Tity (Journal of English Language and Education, 2025)
The aim of this research is to: (1) Find out the analysis of teacher and student needs for the development of reflective picture storybook media (2) Find out the design for developing socio-cultural-based reflective picture storybook media (3) Find out the feasibility of socio-cultural-based reflective picture storybook media (4) and find out the effectiveness of using socio-cultural-based reflective picture storybook media to improve social skills and reading interest in grade IV elementary school students in Kersana District, Brebes. This type of research is research and development to produce sociocultural-based reflective picture storybook media to improve social skills and reading interest of fourth grade elementary school students. This research refers to the ADDIE development model from Dick and Carry. Data collection techniques using questionnaires, interviews, observations and documentation. The population in this study were fourth grade elementary school students in Kersana District with a sample of 6 schools divided into control classes and experimental classes. Data analysis techniques used were normality tests, homogeneity tests, t tests and feasibility tests and media effectiveness.The results of the study showed that there was an influence of reflective picture storybook media on social skills and reading interest of grade IV elementary school students in Kersana District, Brebes, in this case the media was positive and had a significant influence. The conclusion that can be obtained based on this study is the analysis of teacher and student needs for media includes analysis of student needs, user analysis, analysis of facilities and infrastructure. Knowing the design of media development consists of media selection, format selection, compilation of questions and answers and designing application media. The feasibility of media from three validators obtained material validation of 93%. While in the media aspect obtained an average of 92%. The effectiveness of the use of learning media is proven by student learning outcomes between the results of the pre-test and post-test of the experimental class which increased from 14% to 83%. This proves that media has a significant effect on students' social skills and reading interests.